2022
DOI: 10.1001/jamanetworkopen.2022.33649
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of an Emergency Department–Based Intensive Care Unit

Abstract: ImportanceValue in health care is quality per unit cost (V = Q/C), and an emergency department–based intensive care unit (ED-ICU) model has been associated with improved quality. To assess the value of this care delivery model, it is essential to determine the incremental direct cost of care.ObjectiveTo determine the association of an ED-ICU with inflation-adjusted change in mean direct cost of care, net revenue, and direct margin per ED patient encounter.Design, Setting, and ParticipantsThis retrospective eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…As boarding of non‐ICU/general care patients in the ED may continue to be a widespread issue, recognition of decompensation and developing pathways to deliver timely, high‐quality care to these patients is paramount. An ED‐ICU model can deliver early coordinated critical care and likely mitigate preventable complications of disease progression 14 . Future work can evaluate the impact of ED‐ICUs on outcomes at other institutions, including additional methods of caring for decompensating boarding patients.…”
Section: Discussionmentioning
confidence: 99%
“…As boarding of non‐ICU/general care patients in the ED may continue to be a widespread issue, recognition of decompensation and developing pathways to deliver timely, high‐quality care to these patients is paramount. An ED‐ICU model can deliver early coordinated critical care and likely mitigate preventable complications of disease progression 14 . Future work can evaluate the impact of ED‐ICUs on outcomes at other institutions, including additional methods of caring for decompensating boarding patients.…”
Section: Discussionmentioning
confidence: 99%
“…Best practice consideration to develop step-down units, long-term care units, and tele-ICUs comes with an emphasis on ensuring appropriate sta ng, adequate resources, and robust governance process. On the other hand, previously published literature is equivocal with regards to endorsing other speciality ICUs (e.g., surgical intermediate care units, emergency department-based ICU) manned by non-ICU teams, despite the availability of positive studies [5,30,43]. This hesitancy may be due to concerns regarding quality of care being provided by non-ICU teams and highlights the need to ensure standardization irrespective of clinical team involved.…”
Section: Discussionmentioning
confidence: 99%
“…2. Infrastructure fundamentals: Implementing evidence-based care, information technology best practices, e cient care delivery, and the sustainable use of resources [30][31][32][33]. 3.…”
Section: Expert Panelmentioning
confidence: 99%
“…patients after major elective surgery or those deteriorating on hospital wards). An economic analysis revealed that critical care delivery in the ED is cost-effective [ 18 ], a finding that is of particular importance in healthcare systems with payment-per-diagnosis reimbursement.…”
mentioning
confidence: 99%